Classifying perianal fistulising Crohn's disease: an expert consensus to guide decision-making in daily practice and clinical trials. (June 2022) - Geldof, Jeroen; Iqbal, Nusrat; LeBlanc, Jean-Frédéric; Anandabaskaran, Sulak; Sawyer, Rachel; Buskens, Christianne; Bemelman, Willem; Gecse, Krisztina; Lundby, Lilli; Lightner, Amy L; Danese, Silvio; Spinelli, Antonino; et al.
Summary: Perianal fistulising Crohn's disease is an aggressive disease phenotype that can have a substantial detrimental impact on patients' quality of life. Current biological understanding of perianal fistulising Crohn's disease remains inadequate and previous classification systems have not provided clear guidance on therapy in clinical practice nor on defining patient cohorts within clinical trials. We propose a new classification system for perianal fistulising Crohn's disease that was developed through a modified nominal group technique expert consensus process. The classification identifies four groups of patients. Key elements include stratification according to disease severity as well as disease outcome; synchronisation of patient and clinician goals in decision making, with a proactive, combined medical and surgical approach, on a treat to patient goal basis; and identification of indications for curative fistula treatment, diverting ostomy, and proctectomy. The new classification retains an element of flexibility, in which patients can cycle through different classes over time. Furthermore, with each specific class comes a paired treatment strategy suggestion and description of clinical trial suitability. The proposed classification system is the first of its kind and is an important step towards tailored standardisation of clinical practice and research in patients with perianal fistulising Crohn's disease.